2008
DOI: 10.1016/j.neunet.2008.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Robotics and neuroscience: A rhythmic interaction

Abstract: a b s t r a c tAt the crossing between motor control neuroscience and robotics system theory, the paper presents a rhythmic experiment that is amenable both to handy laboratory implementation and simple mathematical modeling. The experiment is based on an impact juggling task, requiring the coordination of two upper-limb effectors and some phase-locking with the trajectories of one or several juggled objects. We describe the experiment, its implementation and the mathematical model used for the analysis. Our u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…These conclusions were derived from a mathematical model of the task where stability analyses of the periodic behavior provided support that subjects exploited stability of the rhythmic task. Establishing dynamic stability in the ball-racket system makes extensive error corrections unnecessary and makes control less costly (Ronsse et al 2008a). This is consistent with the sub-jective observation that in skilled performance less attention is needed to maintain a stable pattern.…”
Section: Introductionmentioning
confidence: 99%
“…These conclusions were derived from a mathematical model of the task where stability analyses of the periodic behavior provided support that subjects exploited stability of the rhythmic task. Establishing dynamic stability in the ball-racket system makes extensive error corrections unnecessary and makes control less costly (Ronsse et al 2008a). This is consistent with the sub-jective observation that in skilled performance less attention is needed to maintain a stable pattern.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent investigations revealed that the interaction between rhythmic and discrete components is necessary to finely control an external object (a bouncing ball), either to correct for unexpected perturbations (Wei, Dijkstra, & Sternad, 2007) or to adapt the control strategy to various movement frequencies or visual feedback conditions (Ronsse, Lefèvre, & Sepulchre, 2008; Ronsse, Thonnard, Lefèvre, & Sepulchre, 2008). Taken together, these findings suggest that even if they are largely nonoverlapping primitives, discrete and rhythmic movements are combined in a nonarbitrary manner by the central nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…A first study applied perturbations and showed that return to steady state is faster than relying on self-correction only (Wei et al 2007, 2008). But also at steady state, theoretical analyses provided a way to tease apart indicators of closed-loop control from dynamically stable performance (Wei et al 2007; Ronsse et al 2008a, b; Wei et al 2008). Interestingly, the relative contribution of active and passive contributions changed with experience: more experienced actors relied more on dynamical stability but, at the same time, also showed more active error corrections.…”
Section: Introductionmentioning
confidence: 99%